Cryptochrome Is a Regulator of Synaptic Plasticity in the Visual System of Drosophila melanogaster - Damulewicz, Milena (Front Mol Neurosci, 2017)
Drosophila CRYPTOCHROME (CRY) is a blue light sensitive protein with a key role in circadian photoreception. A main feature of CRY is that light promotes an interaction with the circadian protein TIMELESS (TIM) resulting in their ubiquitination and degradation, a mechanism that contributes to the synchronization of the circadian clock to the environment. Moreover, CRY participates in non-circadian functions such as magnetoreception, modulation of neuronal firing, phototransduction and regulation of synaptic plasticity. In the present study we used co-immunoprecipitation, yeast 2 hybrid (Y2H) and in situ proximity ligation assay (PLA) to show that CRY can physically associate with the presynaptic protein BRUCHPILOT (BRP) and that CRY-BRP complexes are located mainly in the visual system. Additionally, we present evidence that light-activated CRY may decrease BRP levels in photoreceptor termini in the distal lamina, probably targeting BRP for degradation.